Isolation and Functional Characterization of Endophytic Bacteria from Muscadine Grape Berries: A Microbial Treasure Trove - Meenakshi Agarwal; Mehboob B. Sheikh (Cells)
Muscadine grapes are renowned for their unique traits, natural disease resistance, and rich bioactive compounds. Despite extensive research on their phytochemical properties, microbial communities, particularly endophytic bacteria, remain largely unexplored. These bacteria play crucial roles in plant health, stress tolerance, and ecological interactions. This study represents the first comprehensive effort to isolate, identify, and functionally characterize the bacterial endophytes inhabiting muscadine grape berries using a culture-dependent approach. We isolated diverse bacterial species spanning six genera—Bacillus, Staphylococcus, Paenibacillus, Calidifontibacillus, Curtobacterium, and Tatumella. Microscopic and physiological analysis revealed variations in bacterial morphology, with isolates demonstrating adaptability to varied temperatures. Cluster-based analysis indicated functional specialization among the isolates, with species from Pseudomonadota and Actinomycetota exhibiting superior plant growth-promoting abilities, whereas Bacillota species displayed potential biocontrol and probiotic properties. Among them, Tatumella ptyseos demonstrated exceptional plant growth-promoting traits, including indole-3-acetic acid production, nitrogen fixation, phosphate solubilization, and carbohydrate fermentation. Additionally, Bacillus spp. showed presumptive biocontrol potential, while Paenibacillus cineris emerged as a potential probiotic candidate. The identification of Calidifontibacillus erzurumensis as a novel endophytic species further expands the known biodiversity of grape-associated microbes. These findings provide insights into the metabolic diversity and functional roles of muscadine grape-associated endophytes, highlighting their potential for agricultural and biotechnological applications.